Interactive economics learning with audio-visual media (Sales Ratio Assessment case study) - Damas Dwi Anggoro; Tommy Anggriawan; Deni Agus Setyono (Himpunan Pengembang Kurikulum Indonesia, 2024)
Tax education in secondary or vocational schools has an essential role in forming a good understanding of the tax system. This research aims to increase students' understanding of the Assessment Sales Ratio (ASR) method in economics learning through audio-visual media. ASR, often used in property valuation for tax purposes, was selected as a case study. The audio-visual media used includes video tutorials and interactive quizzes. Video tutorials are designed to explain ASR concepts and applications with engaging animations and diagrams, while interactive quizzes test students' understanding after watching the videos. This research uses a Research and Development (RnD) approach to develop and test the effectiveness of this learning media. The research results show that using audio-visual media can increase students' understanding significantly compared to traditional teaching methods. Student feedback also shows that audio-visual media makes learning more interesting and easier to understand. These findings indicate that integrating audio-visual media in economics learning can effectively overcome difficulties in understanding complex concepts. The recommendation of this research is the further development of interactive educational content for economics and accounting subjects at the secondary school level. Abstrak Pembelajaran perpajakan di sekolah menengah atau kejuruan memiliki peranan penting dalam membentuk pemahaman yang baik tentang sistem perpajakan. Penelitian ini bertujuan untuk meningkatkan pemahaman siswa tentang metode Assessment Sales Ratio (ASR) dalam pembelajaran ekonomi melalui penggunaan media audio visual. ASR, yang sering digunakan dalam penilaian properti untuk keperluan perpajakan, dipilih sebagai studi kasus. Media audio visual yang digunakan meliputi video tutorial dan kuis interaktif. Video tutorial dirancang untuk menjelaskan konsep dan aplikasi ASR dengan animasi dan diagram yang menarik, sementara kuis interaktif menguji pemahaman siswa setelah menonton video. Penelitian ini menggunakan pendekatan Research and Development (RnD) untuk mengembangkan dan menguji efektivitas media pembelajaran tersebut. Hasil penelitian menunjukkan bahwa penggunaan media audio visual dapat meningkatkan pemahaman siswa secara signifikan dibandingkan dengan metode pengajaran tradisional. Umpan balik siswa juga menunjukkan bahwa media audio visual membuat pembelajaran lebih menarik dan mudah dipahami. Temuan ini mengindikasikan bahwa integrasi media audio visual dalam pembelajaran ekonomi dapat menjadi solusi efektif untuk mengatasi kesulitan dalam memahami konsep yang kompleks. Rekomendasi penelitian ini adalah pengembangan lebih lanjut dari konten pendidikan interaktif untuk mata pelajaran ekonomi dan akuntansi di tingkat sekolah menengah. Kata Kunci: media audio visual; nilai jual objek pajak; penilaian rasio penjualan (ASR)